2014
DOI: 10.1007/s11596-014-1258-4
|View full text |Cite
|
Sign up to set email alerts
|

Effects of notch-1 down-regulation on malignant behaviors of breast cancer stem cells

Abstract: This study examined the effect of Notch-1 signaling on malignant behaviors of breast cancer cells by regulating breast cancer stem cells (BCSCs). BCSCs were enriched by using serum-free medium and knocked out of Notch-1 by using a lentiviral vector. Real-time polymerase chain reaction (RT-PCR) and Western blotting were used to detect the Notch-1 expression levels in breast cancer cell lines and BCSCs, and flow cytometry to detect the proportion of BCSCs in BCSC spheres. The BCSC self-renewal, migration, invasi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
8
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 20 publications
1
8
0
Order By: Relevance
“…This is consistent with the finding that MDA-9/Syntenin is highly expressed in the reservoir of interfollicular stem cells [82]. However, the relationship between MDA-9/Syntenin and Notch signaling has not been fully explored in other settings, including breast cancer, in which this pathway can be a promoter of tumor stem cell activity and invasion [92,93]. …”
Section: Directing Cellular Traffic: Role As Intracellular Adaptersupporting
confidence: 84%
“…This is consistent with the finding that MDA-9/Syntenin is highly expressed in the reservoir of interfollicular stem cells [82]. However, the relationship between MDA-9/Syntenin and Notch signaling has not been fully explored in other settings, including breast cancer, in which this pathway can be a promoter of tumor stem cell activity and invasion [92,93]. …”
Section: Directing Cellular Traffic: Role As Intracellular Adaptersupporting
confidence: 84%
“…Notch-1 was linked to diverse cellular processes including cell proliferation, apoptosis, and cancer metastasis and angiogenesis [44]. Recently, Notch-1 was reported to take part in the regulation of malignant behaviors of breast cancer stem-like cells [45]. Moreover, Xu et al [46] demonstrated that by interacting with the Akt signaling pathways, Notch-1 is involved in the growth and tumorgenesis of GSCs in vitro and in vivo.…”
Section: Discussionmentioning
confidence: 99%
“…TGF-β induces cell cycle to arrest in G0/G1 phase, and in the TGF-β signaling pathway STIM1 and store-operated calcium entry (SOCE) play an anti-proliferative role in breast cancer [15]. In addition, more and more evidences have shown that Notch1 overexpression is strongly associated with breast cancer invasion, which is an important factor in maintaining the malignant phenotype of breast cancer stem cells [16]. Notchl signaling also correlates with self-renewal and differentiation of breast cancer stem cells (CSCs) and their malignant behaviors [17].…”
Section: Introductionmentioning
confidence: 99%